Specific Features and Ecological Significance of Mosses - Marat, Nagmetullaev (Journal of Environmental Economics and Sustainability, 2025)
This article examines the role of mosses (Bryophyta) in the ecological system, their chemical composition, and potential uses. The main goal of the research is to determine the role of mosses in ensuring environmental sustainability and to assess the possibilities of their use as bioindicators. Methodologically, methods of literature analysis, empirical research, laboratory experiments, and statistical analysis were used. The research results showed the influence of mosses on soil formation, moisture retention properties, and the possibility of their use in industry. The practical significance lies in the fact that mosses can be used as bioindicators in environmental monitoring systems, as well as in the fields of pharmaceuticals and biotechnology.